(untitled) (Innovative professional education, 2022)
The regulatory and legal support for the training of future PhD at the Institute of Vocational Education of the NAES of Ukraine was considered, in particular the purpose and objectives of the educational discipline «Comparative Vocational (Professional) Pedagogy».